REPRESENTASI PEREMPUAN DI POLITIK: Studi Kasus Anggota Legislatif Perempuan dalam menjalankan Fungsinya di DPRD Provinsi Nusa Tenggara Timur - Rex Tiran; Diana S.A.Natalia Tabun; Rouwland A. Benyamin; Johannes Fisher Keon (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2023)
The political representation of women sticks out in the midst of domination and hegemony of patriarchal culture in various dimensions of life, especially in the political space. There is a kind of socio-political obstacle that forces women to double their capital and power, which must be spent more heavily and complicated than men when they enter politics. This study wants to see how far the role of women legislators in the NTT Provincial DPRD for the 2019-2024 period is in carrying Political parties and are in accordance with the interests of the categorization of women members of the legislature. The strategy for dividing positions for women is also quite diverse. Women have political hopes that are placed on increasing access power and opening up political opportunities to occupy strategic positions such as important positions or involvement in the decision-making process in political parties. The hope for increasing access is related to increasing the capacity of individual women and youth in political parties. Increasing women's access to strategic positions in political parties. This political hope emphasizes the importance of women and youth to have economic, social and political capacities. Economic capacity relates to financial resources, social capacity refers to social relations and networks, and political capacity relates to political knowledge and skills